Natural Language Processing for Automated Customer Service in Banking - Mohammed, Manzoor Anwar (Global Disclosure of Economics and Business, 2021)
NLP integration into automated banking customer care systems is examined for its effects on customer experience and operational efficiency. The main goals are to assess NLP's effects on customer happiness, reaction times, and accuracy and identify its limits. Secondary data compares satisfaction levels, response times, and mistake rates before and after NLP's implementation. NLP enhances customer satisfaction and operational efficiency, particularly for routine queries and transactions. Complex problems and technical aid need human intervention, making management challenging. Privacy and data security are also important. Policy implications advise strong data security and a balanced strategy combining automated and human help to answer complex inquiries. NLP can improve banking customer service. However, the research suggests more development and deliberate policy implementation.